Exploring the Impact of Affixation, Vocabulary Mastery, and Reading Interest on Students' Comprehension of Authentic Texts: A Study of Third-Semester English Students at University - Indah Pertiwi; Jufrizal Jufrizal (STAI Hubbulwathan Duri, 2025)
Reading comprehension of authentic texts is influenced by various linguistic and motivational factors. This study investigated the contributions of affixation mastery, vocabulary mastery, and reading interest to the reading comprehension of third-semester English students. A correlational research design with multiple regression analysis was employed. The participants were 55 third-semester English students at STAIN Mandailing Natal. Data were collected using objective tests to assess affixation and vocabulary mastery, and a questionnaire to measure reading interest. Descriptive and inferential statistics, including hypothesis testing and regression analysis, were conducted using Minitab version 22. The analysis revealed that affixation mastery significantly contributed to students’ reading comprehension (p = 0.002). Vocabulary mastery (p = 0.001) and reading interest (p = 0.000) also showed significant positive contributions. Collectively, the three variables accounted for 43.53% of the variance in reading comprehension, indicating a substantial combined influence. The remaining 56.47% of the variance was attributed to other unexamined factors. These findings suggest that both linguistic competencies and motivational aspects are critical in enhancing students' comprehension of authentic texts. The study emphasizes the need for instructional strategies that support morphological awareness, vocabulary development, and the cultivation of reading interest to improve reading outcomes in EFL contexts.